Jum’at Berkah and the Tradition of Islamic Philanthropy: Anthropolinguistic Study of Sego Jum’at at the Jogokariyan Mosque, Yogyakarta - Mahmudah; Satibi, Ibi; Zaini, Hisyam; Holilulloh, Andi (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
Religious language has become part of social life. Apart from functioning as an expression of religious devotion, religious language also contains the meaning of internalizing religious virtue, which has implications for social piety. This research aims to describe the Jum’at Berkah tradition at the Jogokariyan Mosque in Yogyakarta. This socioreligious tradition has strong roots in the doctrine of philanthropy and takes advantage of the momentum of Friday as a day that is believed to contain many blessings. Methodologically, this research utilizes qualitative research procedures and data collection through observation and interviews. By utilizing an anthropolinguistic perspective, this research finds several conclusions. First, the Jum’at Berkah tradition carried out at the Jogokariyan Mosque in Yogyakarta, is a cultural phenomenon of Muslim society closely related to the muscular and implicative elements of the Islamic language. Environmental, social, and religious understanding factors contribute to implementing Jum’at Berkah through Sego Jum’at. The use of the term Jum’at Berkah in giving charities is based on people's religious understanding. It explains that Friday is sayyidul ayyam, a good day, and distinguishes it from other days. Second, Jum’at Berkah has a religious impact with a socio-economic dimension, specifically increasing people's awareness of sharing, strengthening brotherhood ties with fellow humans, and competing to do kindness.